Rancang Bangun Aplikasi Laporan Keuangan Swalayan 89 Berbasis Dekstop - Dewi Fajar Ayu; Jamal Rusdiana; Ninanesia Rusdiana (Journal Of Informatics And Busisnes, 2025)
In the digital era, information technology plays a crucial role in enhancing operational efficiency and effectiveness across various sectors, including financial management in retail businesses. Swalayan 89, as a growing retail business unit, still relies on manual recording of financial transactions. This practice may lead to recording errors, delayed reporting, and difficulties in preparing accurate and timely financial statements. This study aims to design and develop a desktop-based financial reporting application using Visual FoxPro 9.0. The application is expected to automate transaction recording processes, improve accuracy, speed up reporting, and support data-driven decision-making in a more efficient and real-time manner. The application is developed using the System Development Life Cycle (SDLC) with the Waterfall model, which includes the stages of Requirement, Design, Implementation, Testing (Blackbox), and Maintenance. Data collection techniques include observation, interviews, and literature study. With the implementation of this application, Swalayan 89 is expected to have a better-organized financial system, minimize recording errors, improve work efficiency, and adapt to the needs of a digitalized system.